Optimizing MRI Examination Planning through a Computational Formula: A Mixed-Method Study of Radiology Management in Indonesian Hospitals - Gatot Santosa; Bambang Satoto; Rini Indrati; Edy Susanto; Tri Asih Budiati; Ahmad Hariri (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. The healthcare sector is a fundamental aspect of human life, requiring continuous attention from governments to improve service quality. In radiology services, particularly Magnetic Resonance Imaging (MRI), optimizing resource use is crucial due to high equipment costs and the complexity of operations. Purpose. This study develops a computational formula designed to assist radiology department heads in planning and calculating daily MRI examination targets during the equipment's lifespan. Factors such as hospital type, service fees, operational costs, and regional location are incorporated into the formula. Method. The research employs a mixed-method approach, combining preliminary surveys with the development and validation of the computational formula. Validation by financial and radiology experts demonstrated the formula's reliability and accuracy. Additionally, large-scale testing involving ten stakeholders confirmed the application's functionality, reliability, and user-friendliness. Results. The Results show that this tool significantly improves the planning and operational management of MRI equipment, offering a solution that is adaptable to new regulations and real-time data. Conclusion. This application provides a promising method for optimizing MRI use in hospitals, particularly within the context of the National Health Insurance (JKN) system. Its flexibility and ease of use make it applicable for both government and private hospitals, ensuring effective MRI utilization and financial management.